Near-infrared spectroscopy of extreme BAL QSOs from the QUBRICS bright quasar survey. Issue 2 (17th December 2021) - Cupani, Guido; Calderone, Giorgio; Selvelli, Pierluigi; Cristiani, Stefano; Boutsia, Konstantina; Grazian, Andrea; Fontanot, Fabio; Guarneri, Francesco; D'Odorico, Valentina; Giallongo, Emanuele; Menci, Nicola
ABSTRACT: We report on the spectral confirmation of 18 quasi-stellar object (QSO) candidates from the QUasars as BRIght beacons for Cosmology in the Southern hemisphere (QUBRICS) survey, previously observed in the optical band, for which we acquired new spectroscopic data in the near-infrared band with the Folded-port InfraRed Echellette (FIRE) spectrograph at the Magellan Baade telescope. In most cases, further observations were prompted by the peculiar nature of the targets, whose optical spectra displayed unexpected absorption features. All candidates have been confirmed as bona fide QSOs, with average emission redshift z ≃ 2.1. The analysis of the emission and absorption features in the spectra, performed with astrocook and QSFit, reveals that the large majority of these objects are broad absorption line (BAL) QSOs, with almost half of them displaying strong Fe ii absorption (typical of the so-called FeLoBAL QSOs). The detection of such a large fraction of rare objects (which are estimated to account for less than 1 per cent of the general QSO population) is interpreted as an unexpected (yet favourable) consequence of the particular candidate selection procedure adopted within the QUBRICS survey. The measured properties of FeLoBAL QSOs observed so far provide no evidence that they are a manifestation of a particular stage in active galactic nucleus (AGN) evolution. In this paper, we present an explorative analysis of the individual QSOs, to serve as a basis for a further, more detailed investigation.